Barriers and Facilitators Affecting Tuberculosis Infection Control Practices of Russian Health Care Workers - Woith, Wendy Mann (2012)
SETTING: Five inpatient and outpatient tuberculosis care facilities in two regions of Russia. Objective: To identify barriers and motivators to use of infection control measures among Russian TB health care workers. DESIGN: In this qualitative study, a convenience sample of 96 HCWs was used to generate 15 homogeneous focus groups consisting of physicians, nurses, lab staff, or support staff. RESULTS: Barriers and motivators related to knowledge, attitudes and beliefs, and practices were identified. Three main barriers were a) knowledge deficits, including the belief that TB was transmitted by dust, linens, and eating utensils; b) negative attitudes related to the discomfort of respirators; and c) practices with respect to quality and care of respirators. Education and training, fear of infecting loved ones, and fear of punishment were the main motivators. CONCLUSIONS: Our results point to the need for evaluation of current educational programs. Positive health promotion messages that appeal to fear might also be successful in promoting use of TB infection control. Individualized rewards based on personal motivators or group rewards that build on collectivist theory could be explored.